Inside campaign finance : myths and realities - Sorauf, Frank J. (Frank Joseph), 1928-2013 (Yale University Press, 1992)
"How much does money affect the outcome of elections? Do those who help finance candidates exert undue influence in the making of public policy? In this landmark book, one of America's most distinguished political scientists explores the dynamics and consequences of campaign finance in America and explodes many myths about this widely debated subject." "Frank J. Sorauf provides balanced and informative commentary on such critical issues in campaign financing as: the growing problems of regulating American campaign finance under the post-Watergate legislation of 1974; the forces that affect the supply of money available for campaigning, from economic conditions to the competitiveness of elections; the increasing power of incumbent candidates in the two-way exchange between candidates and contributors; political learning and the search for ways to avoid the laws on campaign finance; the myths and realities about the role and influence of PACs; the vanishing funds for public funding of the presidential campaigns; the new middlemen and brokers <e.g., the case of Charles Keating); the major options for reform: private versus public funding; the political deadlock over reform: parties, public opinion, and the interests of incumbents; the possibility of new levels of competition and spending in 1992." "Sorauf argues that the American system of campaign financing has become increasingly stable and institutionalized during the last sixteen years, and that the major players in the system-PACs, individual fundraisers, party committees, and incumbent candidates--now behave in fairly predictable ways. His book is a fresh and persuasive account of the importance and the limits of money as a base of political influence in the United States."--Jacket